Neue Polyphenylensulfone : Reaktionen an festen Polymeren - R. Gabler; J. Studinka (CHIMIA)
A method is described by which aromatic polythioethers containing sulfone groups regularly distributed along the polymer chain are oxidized in solid suspensions quantitatively to polyarylenesulfones of the genereal structure –Ar–SO2–Ar–SO2–Ar–SO2–, Ar being identical or different nuclei such as benzene, naphthalene or diphenyl. Polymers of this type have heretofore not been obtained in a pure state and with high molecular weight.